The neurobiology of pain: (molecular and cellular neurobiology) - Hunt, Stephen P.; Koltzenburg, Martin (Oxford University Press, 2005)
Within the last decade we have seen major new advances in the neurobiology of pain. The topic has emerged as a separate field of study in its own right. This volume presents a state-of-the-art account of the neurobiological basis of pain by leading scientists in this field
Published to Oxford Scholarship Online: January 2010
Includes bibliographical references and index
Gesehen am 05.11.2020
Keywords: Bibliografie; Neurobiologie; Schmerz